A Gap Analysis of Yogyakarta Smart City Project (within the Dimension of Smart Governance and Smart Economy) - Ray Ferza; Melati Ayuning Pranasari; Suci Emilia Fitri; Dian Martha Indarti; Tedi Gunawan (Journal of Governance, 2022)
The COVID 19 Pandemic exposed digitalization as a fundamental aspect to revive the local economy. Fortunately, Indonesia has already shifted towards a 100 Smart City for their Municipalities since 2017. Yogyakarta as one of the best SC, has suffered the impact of pandemic. In the need to explore the phenomenon of how an SC should be implemented within the circumstances, it will be relevant to describe a gap analysis on (1) Yogyakarta SC Project through the dimensions of SG and SE and (2) Strategic Solutions. This paper employed a gap analysis through a qualitative study and it uncovered gaps of the SC project such as central government intervention, sectoral quality of digitalization, and intergovernmental sync. The strategy to eclipse the Cohen SC Wheel are the followings: reinforcing the regulatory capacity, improving the app business process and features, and intensify the formal cooperation, be it inter-governmentally or between public-private.